Case Report: Cognitive Assessment Before an Amnesic Seizure in Transient Epileptic Amnesia Syndrome - Bouyer, Coline; de Toffol, Bertrand (Frontiers in Neurology, 2022)
A patient with transient epileptic amnesia syndrome presented a clinically observable amnesic seizure immediately after a neuropsychological assessment. An hour and a half before the onset of the seizure, the patient progressively developed an isolated alteration of episodic memory. These data question the ictal/interictal distinction in this syndrome as well as the speed of propagation of an epileptic activity.